2013
DOI: 10.1007/s11154-013-9260-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxytocin signaling in the regulation of body weight

Abstract: Obesity and its associated metabolic disorders are growing health concerns in the US and worldwide. In the US alone, more than two-thirds of the adult population is classified as either overweight or obese [1], highlighting the need to develop new, effective treatments for these conditions. Whereas the hormone oxytocin is well known for its peripheral effects on uterine contraction during parturition and milk ejection during lactation, release of oxytocin from somatodendrites and axonal terminals within the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 237 publications
(465 reference statements)
3
78
0
Order By: Relevance
“…Other work has shown a release of oxytocin from somatodendrites and axonal terminals within the CNS implicated in both control of energy balance the formation of prosocial behaviors [41]. Romero et al and Nagasawa et al [16,68] found that giving dogs exogenous oxytocin supplements causes them to display stronger social bonding behavior, both with people and other dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other work has shown a release of oxytocin from somatodendrites and axonal terminals within the CNS implicated in both control of energy balance the formation of prosocial behaviors [41]. Romero et al and Nagasawa et al [16,68] found that giving dogs exogenous oxytocin supplements causes them to display stronger social bonding behavior, both with people and other dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that oxytocin inhibits weight gain in rodent models [21,41], and that oxytocin modulates appetite in human subjects [29], plasma levels of oxytocin were tested in mice of long-and short-term experiments. We found significantly elevated blood plasma oxytocin levels in C57BL/6 mice getting canine-source L. reuteri 2546 in their water, when compared with age-matched controls drinking regular water ( Figures 5A and 5B).…”
Section: Canine Bacteria Induce Neuropeptide Hormone Oxytocinmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin has also been linked to energy homeostasis mechanisms in animals, where it acts as a strong inhibitor of food intake and affects energy expenditure and glucose homeostasis [27][28][29][30][31]. Oxytocin has also been shown to play an important role in metabolism and energy balance in humans [32,33], such as reducing caloric intake with a preferential effect on fat intake [11] and reward-driven food intake in humans [34]. These findings are in line with our finding that reduced levels of delta oxytocin correlate with a high BMI in CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a large body of findings supports a prominent role for oxytocin in the modulation of food intake and body weight in animal models [5].…”
Section: Introductionmentioning
confidence: 92%